WORK TERMINATION DURING THE COVID-19 PANDEMIC IN THE PERSPECTIVE OF POSITIVE LAW IN INDONESIA - Inayah Inayah; Surisman Surisman (Legal Standing : Jurnal Ilmu Hukum, 2020)
The case of work termination which involves businessowners and labor happens widelyin various companies due to the Covid-19 pandemic in Indonesia. This research usesthe normative legal research method. During this Covid-19 pandemic, this worktermination is carried out to save the company and to prevent more victims. Problemswhich happen regarding work termination include the reasons for this termination andthe post-termination compensation. Work relations is a reciprocal relationship which isbased on a two-party agreement. The legal protection for work termination may becarried out during this Covid-19 pandemic. If the rights stated above are not obtainedby the workers, then they may initiate a deliberation. They may also go through conflictresolution procedures on industrial relations outside of court, based on the Republic ofIndonesia’s Constitution No. 2 of 2004.